Religion, politics, and sugar : the Mormon Church, the federal government, and the Utah-Idaho Sugar Company, 1907-1921 - Godfrey, Matthew C. (Utah State University Press, 2007)
"One famous target of Progressive Era attempts to rein in monopolistic big business was the eastern Sugar Trust. Less known is how federal regulators also tried to break monopoly control over beet sugar in the West by going after the Utah-Idaho Sugar Company, a business supported and controlled by the Latter-day Saints church and run by Mormon authorities. As sugar beet agriculture boomed, the Mormon church's involvement led directly to monopolistic practices by Utah-Idaho Sugar and to federal investigations. Church leaders encouraged members, a majority population in much of the intermountain West, to patronize the company exclusively, as suppliers and consumers. As early as 1890, Mormon church president Wilford Woodruff had called missionaries to raise money for the fledgling company and asserted divine inspiration for church support. Utah-Idaho bridged the cooperative, theocratic, self-sufficient economic model of nineteenth-century Mormonism and the integration of the Mormon West into the national market economy. Religion, Politics, and Sugar shows, through the example of an important western business, how national commercial, political, and legal forces in the early twentieth century came west and, more specifically, how they affected the important role the Mormon church played in economic affairs in the region."--Publisher's abstract